Galectin‐3 modulates postnatal subventricular zone gliogenesis. Issue 2 (18th October 2019) - Al‐Dalahmah, Osama; Campos Soares, Luana; Nicholson, James; Draijer, Swip; Mundim, Mayara; Lu, Victor M.; Sun, Bin; Tyler, Teadora; Adorján, István; O'Neill, Eric; Szele, Francis G.
Abstract: Postnatal subventricular zone (SVZ) neural stem cells generate forebrain glia, namely astrocytes and oligodendrocytes. The cues necessary for this process are unclear, despite this phase of brain development being pivotal in forebrain gliogenesis. Galectin‐3 (Gal‐3) is increased in multiple brain pathologies and thereby regulates astrocyte proliferation and inflammation in injury. To study the function of Gal‐3 in inflammation and gliogenesis, we carried out functional studies in mouse. We overexpressed Gal‐3 with electroporation and using immunohistochemistry surprisingly found no inflammation in the healthy postnatal SVZ. This allowed investigation of inflammation‐independent effects of Gal‐3 on gliogenesis. Loss of Gal‐3 function via knockdown or conditional knockout reduced gliogenesis, whereas Gal‐3 overexpression increased it. Gal‐3 overexpression also increased the percentage of striatal astrocytes generated by the SVZ but decreased the percentage of oligodendrocytes. These novel findings were further elaborated with multiple analyses demonstrating that Gal‐3 binds to the bone morphogenetic protein receptor one alpha (BMPR1α) and increases bone morphogenetic protein (BMP) signaling. Conditional knockout of BMPR1α abolished the effect of Gal‐3 overexpression on gliogenesis. Gain‐of‐function of Gal‐3 is relevant in pathological conditions involving the human forebrain, which is particularly vulnerable to hypoxia/ischemia during perinatal gliogenesis. Hypoxic/ischemic injury induces astrogliosis, inflammation and cell death. We show that Gal‐3 immunoreactivity was increased in the perinatal human SVZ and striatum after hypoxia/ischemia. Our findings thus show a novel inflammation‐independent function for Gal‐3; it is necessary for gliogenesis and when increased in expression can induce astrogenesis via BMP signaling. Main points: Gal‐3 loss decreased SVZ‐striatal gliogenesis, whereas overexpression increased it. Gal‐3 bound BMPr1‐α, increased BMP signaling and influenced glial fate choice. Gal‐3 was increased in human perinatal hypoxia/ischemia.